The Impact of Multiple Recesses on Limb Movement Patterns in Children: An Exploratory Study - Webb, G. Kate; Rhea, Deborah J. (International Journal of Child Health and Nutrition, 2023)
Background: Inactivity levels among elementary-aged children are climbing at alarming rates, as only 24% participate in the recommended 60 minutes of daily physical activity. Limb movements during children’s active time are essential for heart, bone, and muscle health, setting the stage for an overall active and healthy life. School recess, defined as child-directed, outdoor play, is optimal for children to accumulate many types and repetitions of limb movements. Therefore, the purpose of this study was to use the Movement Pattern Observation Tool (MPOT) to determine the impact of varying amounts of daily recess on elementary-aged children’s limb movement patterns. It was hypothesized that children who participate in 60 minutes of daily recess would accumulate significantly more limb movements and specifically, contralateral movements as they advance in grades. Methods: This cross-sectional, observational study used the MPOT to observe grades K-2 children from two schools offering one twenty-minute recess daily and two schools offering four 15-minute recesses daily. The researchers observed 3,023 children’s limb movements during recess across the schools. There were 36 total observation scans completed for the four schools observed. Results: Children who received 60 minutes of recess maintained significantly higher activity levels and contralateral movements as they advanced by grade. Additionally, on average 96% of all children utilized unilateral, bilateral, or contralateral limb movements when observed. Conclusion: When given the opportunity, most children will utilize recess in a way that is beneficial for off-setting inactivity trends and is instrumental for a healthy mind-body connection as they age.